Increased burden of rare variants in GWAS associated genes in familial multiple sclerosis - Aleksander Turk; Aleš Maver; Peter Juvan; Jelena Drulović; Šarlota Mesaroš; Ivana Novaković; Nada Starčević Čizmarević; Smiljana Ristič; Ivana Stanković Matić; Borut Peterlin (Scientific Reports)
Abstract Multiple sclerosis (MS) is an immune-mediated neurodegenerative disease affecting the central nervous system with many known genetic risk factors. Although genome-wide association studies (GWAS) have identified common genetic variants with small effects associated with MS, the role of rare variants with large effects in MS aetiology remains underexplored. We hypothesized that rare variants in MS-associated genes from GWAS studies (GWAS-associated genes) are more likely to contribute to familial MS (FMS) risk than to sporadic MS (SMS). Therefore, we aimed to assess the burden of rare, predicted pathogenic (RPP) variants in GWAS-associated genes in FMS and SMS patients compared to controls. Rare genetic variants in 111 GWAS-associated genes were assessed in 87 FMS, 89 SMS and 3866 control cases. We demonstrate that RPP variants were significantly overrepresented in the FMS cohort whereas their frequency was not increased in the SMS cohort compared to controls (p-values 5.27 × 10 − 74 and 1.00, respectively). Six genes (ALPK2, ANKRD55, INTS8, IQCB1, JADE2, and MALT1) significantly contributed to the burden of RPP in the FMS group. We conclude that rare variants in genes identified by GWAS might contribute to the genetic predisposition of familial MS patients.